KEMAJUAN PENELITIAN INDUKSI DAN PEMANJANGAN TUNAS MERBAU (INTSIA BIJUGA [COLEBR.] O. KUNTZE) SECARA IN VITRO - Ramadhani, Latifah Esti; Husin, Arief; Sisunandar, Sisunandar (Universitas Sebelas Maret, 2014)
Abstract - Merbau is one of the high-quality timber tree with the demanding of international market increase every year. However, the over-exploitation of the tree put merbau as a vulnerable species in the future years. Moreover, seedling production of merbau using traditional technique showed several limitationsÂ due to the low number of seed production every year. One of the most promising technique for mass seedling production of merbau is using shoot-tip culture. However, the protocol of shoot-tip culture is remain under develop with low success rate of shoot induction (less then 15 %), without protocols on shoot multiplication, root induction and acclimatisation. Our research at the Laboratory of Botany and Genetics, University of Muhammadiyah Purwokerto showed that the axillary buds isolated from 1-month seedlings can be maintained to induce shoot formation and elongation on the DKW medium (Driver and Kuniyuki, 1984) supplemented with 10-8 M kinetin. Two new shoots started to elongate from each explant after 4 weeks culture (60 % success rate) with each shoot has the lenght of c.a. 4 cm and 4 internode. The inducted shoots were then cut them of into four new axilary buds and subcultured onto the same medium every two week for shoots multiplication. The next step of shoot-tip culture technique, root induction and acclimatization stages is remain developed.Â Keywords : kinetin, shoot-tip culture,multiplication,micropropagation.